2016
DOI: 10.1186/s12885-016-2437-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 signaling in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) incidence is highest in highly developed countries and it is the seventh most common neoplasm diagnosed. RCC management include nephrectomy and targeted therapies. Type 1 insulin-like growth factor (IGF-1) pathway plays an important role in cell proliferation and apoptosis resistance. IGF-1 and insulin share overlapping downstream signaling pathways in normal and cancer cells. IGF-1 receptor (IGF1R) stimulation may promote malignant transformation promoting cell proliferation, dediff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 116 publications
3
43
0
Order By: Relevance
“…IGF-1R is a transmembrane tyrosine kinase receptor of the insulin receptor family and contains two extracellular α subunits and two transmembrane β subunits (45). Numerous studies have reported that IGF-1R is frequently overexpressed in a variety of human cancer types, including gastric cancer (46), breast cancer (47), glioblastoma (48), renal cell carcinoma (49) and osteosarcoma (50). In NSCLC, IGF-1R expression has been revealed to be upregulated, and significantly associated with tumor size, tumor grade and response to chemotherapy (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R is a transmembrane tyrosine kinase receptor of the insulin receptor family and contains two extracellular α subunits and two transmembrane β subunits (45). Numerous studies have reported that IGF-1R is frequently overexpressed in a variety of human cancer types, including gastric cancer (46), breast cancer (47), glioblastoma (48), renal cell carcinoma (49) and osteosarcoma (50). In NSCLC, IGF-1R expression has been revealed to be upregulated, and significantly associated with tumor size, tumor grade and response to chemotherapy (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…p53 is one of the most frequently mutated tumor suppressors and IGF1R overexpression inhibits wild-type p53 (WT-p53) via phosphorylated (p) AKT (80). This enhances the ubiquitination-promoting function of murine double minute 2, which decreases p53 protein production (79). Reciprocally, WT-p53 renders tumor cells more chemosensitive by inhibiting Sp1-induced transactivation of the IGF1R promoter and increasing the expression of pro-apoptotic protein p21 (81).…”
Section: Igf1r and Chemotherapy Resistancementioning
confidence: 99%
“…Previous studies have indicated that cancer chemotherapy is associated with inducing p53-dependent apoptosis responses (79). p53 is one of the most frequently mutated tumor suppressors and IGF1R overexpression inhibits wild-type p53 (WT-p53) via phosphorylated (p) AKT (80).…”
Section: Igf1r and Chemotherapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This protein is produced by adipose cells and affects the negative feedback regulation of glucose transporter type 4, which leads to a decreased insulin sensitivity in fat and other tissues (5). Insulin-like growth factor-1 (IGF-1), which is also a prognostic RCC factor at the time of diagnosis, may be a potential mediator between obesity and RCC development (6). However, the relationship between RBP4 and RCC has not been sufficiently tested.…”
mentioning
confidence: 99%